Development and optimization of nano-hydroxyapatite encapsulating tocotrienol-rich fraction formulation using response surface methodology - Mohd Zaffarin, Anis Syauqina; Ng, Shiow Fern; Ng, Min Hwei; Hassan, Haniza; Alias, Ekram (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Background/Objective: The tocotrienol-rich fraction (TRF) is a lipid-soluble vitamin that has good antioxidant and anti-inflammatory properties. The TRF is widely studied as a potential treatment for various diseases, including bone diseases. However, its application is limited due to its poor oral bioavailability profile, warranting an innovative approach to overcome its pharmacokinetic limitations. Recently, the nano-hydroxyapatite (nHA) has been investigated as a drug delivery vehicle for various drugs and active compounds owing to its excellent biocompatibility, biodegradability, and osteogenic properties. The nHA is also a well-known biomaterial which has chemical and structural similarities to bone minerals. Hence, we aim to explore the use of the nHA as a potential nanocarrier for the TRF. Methods: In this study, we develop and optimize the formulation of an nHA-encapsulating TRF (nHA/TRF) by employing the response surface methodology (RSM). Results: RSM outcomes reveal that the mass of the nHA, the concentration of the TRF, and the incubation time have a significant effect on the particle size, zeta potential, and encapsulation efficiency of the nHA/TRF. The outcomes for the optimized formulation are not significantly different from the predicted RSM outcomes. The optimized nHA/TRF formulation is freeze-dried and results in an average particle size of ~270 nm, a negative zeta potential value of ~−20 mV, a polydispersity index of <0.4, and an encapsulation efficiency of ~18.1%. Transmission electron microscopy (TEM) shows that the freeze-dried nHA/TRF has a spherical structure. Conclusions: Taken together, the above findings indicate that the nHA may be established as a nanocarrier for efficient delivery of the TRF, as demonstrated by the promising physical properties.